Peran Teknologi terhadap Pendapatan Usaha Mikro pada Event Car Free Day Desa Kalisat - Nurhayati, Nurhayati; Pudjiastutik, Endang Wahyu; Hadi, Abdul (Program Studi Agribisnis, 2023)
The progress of a country can be seen through its economic growth, where Economic Growth is one of the determining indicators of success in economic development. Economic activities are efforts to improve the welfare of society, and with increasing economic growth, the needs of the people can be fulfilled. Micro, Small, and Medium Enterprises (MSMEs) are one of the areas of focus for the government and society at large because MSMEs play an important role. MSMEs are a way to address poverty issues and drive economic growth. Moreover, MSMEs provide another avenue for job creation. Indonesia has a significant number of business players, but there are several factors that can hinder their business activities, such as limited capital, low-quality resources, inefficient production systems, lack of financial management systems, inadequate marketing strategies, and a shortage of business premises. This study aims to analyze and determine the influence of Business Duration, Capital, and Technology on the income of business actors in the CFD event in Kalisat Village. The results of the study show that the variables of Business Duration, Capital, and Technology have a positive effect, and only the Capital variable has a significant impact on the income of business actors.